Relationship between Capital Structure and Financial Performance of Indian Cement Companies - Dr. Lakshmi Devi (Innovative Research Thoughts, 2022)
The capital arrangement decision is the most crucial decision for firms/companies because it marks the profitability and risk of firms and shareholders. The present study inspects the relationship of capital structure with the economic presentation of BSE registered cement companies in India. For achieving the objective of the study, five BSE listed companies of Indian cement industry were taken into sample by using judgemental sampling. Under this study, secondary data relating to capital structure and financial performance were gathered from the annual reports of sampled companies for a period of ten years from 2009-10 to 2018-19. The descriptive statistical tools-average, standard deviation, coefficient of variance, skewness, kurtosis and correlation analysis were applied for analysing the data. The obtained results of this study explicated that capital structure variable- Debt ratio has a negative relationship with financial performance variables - net profit, operating profit, return on assets, return on capital employed, return on equity and return on equity per share in the BSE listed companies of the Indian cement industry.